2008
DOI: 10.1200/jco.2008.16.0259
|View full text |Cite
|
Sign up to set email alerts
|

Monosomal Karyotype in Acute Myeloid Leukemia: A Better Indicator of Poor Prognosis Than a Complex Karyotype

Abstract: MK enables (in addition to CN and CBF) the prognostic classification of two new aggregates of cytogenetically abnormal AML, the unfavorable risk MK-negative category (4-year OS, 26% +/- 2%) and the highly unfavorable risk MK-positive category (4-year OS, 4% +/- 1%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
489
10
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(534 citation statements)
references
References 13 publications
30
489
10
5
Order By: Relevance
“…We cannot explain why our findings are different from those of other investigators [8,13] but we show that our patient cohort behaved as expected when the original IPSS cytogenetic risk stratification was applied [4]. More importantly, we demonstrate the additional value of considering MK as a separate prognostic category, and our observations in this regard are consistent with the adverse prognostic impact of MK in other myeloid malignancies including acute myeloid leukemia and primary myelofibrosis [9,14]. Others have suggested that prognosis was related more with the complexity of karyotype rather than MK [15] and the possibility remains that these observations might be influenced by specific therapy [16].…”
Section: Resultscontrasting
confidence: 51%
See 2 more Smart Citations
“…We cannot explain why our findings are different from those of other investigators [8,13] but we show that our patient cohort behaved as expected when the original IPSS cytogenetic risk stratification was applied [4]. More importantly, we demonstrate the additional value of considering MK as a separate prognostic category, and our observations in this regard are consistent with the adverse prognostic impact of MK in other myeloid malignancies including acute myeloid leukemia and primary myelofibrosis [9,14]. Others have suggested that prognosis was related more with the complexity of karyotype rather than MK [15] and the possibility remains that these observations might be influenced by specific therapy [16].…”
Section: Resultscontrasting
confidence: 51%
“…IPSS-R poor and very poor cytogenetic groups include patients with monosomal karyotype (MK), defined as the presence of two or more autosomal monosomies or a single autosomal monosomy in association with other structural abnormalities [9]. We have previously identified MK as an additional adverse risk factor in MDS patients with complex karyotype [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2B). On the other hand, in addition to the IPSS-R cytogenetic classification, we found monosomal karyotype (MK) according to the criteria of Breems et al [16] also had prognostic significance in MDS patients. In a subgroup of 83 patients with complex (3 or more) chromosomal abnormalities, 66 (79.5%) had MK.…”
Section: Resultsmentioning
confidence: 73%
“…Consistent with prior studies reporting high frequency of NF1 deletions in patients with complex aberrant karyotype [8,9], our study demonstrates a significant association between NF1 deletions and unfavorable cytogenetics, and this association remains statistically significant with monosomal karyotype. This distinct cytogenetic subgroup of AML, defined as two or more distinct autosomal chromosome monosomies or one single autosomal monosomy in the presence of structural abnormalities, provides significantly better prognostic prediction [22]. Haferlach et al [8] recently mentioned higher frequency of NF1 deletions in patients with inv(16)(p13q22)/t(16;16)(p13;q22) (6/37 patients or 16.2%).…”
Section: Discussionmentioning
confidence: 99%